Detection of trypanosome infection in the saliva of tsetse flies and buffy-coat samples from antigenaemic but aparasitaemic cattle - Majiwa, Phelix A.O.; Thatthi, R.; Moloo, S.K.; Nyeko, J.H.P.; Otieno, L.H.; Maloo, S. (Cambridge University Press, 1994)
Relatively simple protocols employing non-radioactive DNA probes have been used for the detection of African trypanosomes in the blood of mammalian hosts and the saliva of live tsetse flies. In combination with the polymerase chain reaction (PCR), the protocols revealed trypanosomes in buffy-coat samples from antigenaemic but aparasitaemic cattle and in the saliva of live, infected tsetse flies. Furthermore, the protocols were used to demonstrate concurrent natural infections of single tsetse flies with different species of African trypanosomes.